2018
DOI: 10.1111/ijac.12884
|View full text |Cite
|
Sign up to set email alerts
|

Surface and cross–section characteristics and friction–wear properties of high velocity oxy fuel sprayed WC–12Co coating

Abstract: A WC–12Co coating was sprayed on H13 hot work mould steel using a high velocity oxy fuel (HVOF). The surface and cross–section morphologies, chemical compositions, and phases of obtained coatings were analyzed using a field emission scanning electron microscope (FESEM), energy dispersive spectrometer (EDS), and X–ray diffraction (XRD), respectively. The friction–wear properties were investigated using a wear test, the wear mechanism of WC–12Co coating was also discussed. The results show that the WC–12Co coati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A large amount of the hard WC phase in the coating is the main reason behind the improvement in the hardness and wear resistance of the coating. In a study by Hui et al [32], a small W2C peak was found in the XRD atlas of the WC-12Co coating, indicating that the decarbonization reaction of WC occurs in HVOF spraying. No new WC phase was found in this study, indicating that the coating was not oxidized or decarburized and the coating quality is great.…”
Section: Microstructure Analysis Of Powder and Coatingsmentioning
confidence: 96%
“…A large amount of the hard WC phase in the coating is the main reason behind the improvement in the hardness and wear resistance of the coating. In a study by Hui et al [32], a small W2C peak was found in the XRD atlas of the WC-12Co coating, indicating that the decarbonization reaction of WC occurs in HVOF spraying. No new WC phase was found in this study, indicating that the coating was not oxidized or decarburized and the coating quality is great.…”
Section: Microstructure Analysis Of Powder and Coatingsmentioning
confidence: 96%
“…Various HVOF hard-coated materials, encompassing metallic composites, nitrides, borides, and carbides, find widespread application across diverse industries. These industries include natural gas and petroleum, power plants, automotive, and mould manufacturing, attesting to the versatility and utility of HVOF coatings [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%